Two new species of the subgenus Cardiobioramix Kaszab (Coleoptera: Tenebrionidae: Bioramix Bates) from the Sichuan Province, China - Li, Yun-Chun; Egorov, L.v.; Shi, Ai-Min (Zootaxa, 2016)
Two new species of darkling beetles (Tenebrionidae: Platyscelidini) belonging to the subgenus Cardiobioramix of the genus Bioramix are described. The first one, B. (C.) jinchuanensis sp. nov. known from the Chinese Province Sichuan Jinchuan, is characterized by the elongated parameres which are uniquely curved near the apex. The second one, B. (C.) maoxianensis sp. nov. described from Sichuan Maoxian and can be distinguished from the closely related B. (C.) szetschuana, B. (C.) kulzeri and B. (C.) subaenescens by the basally parallel parameres. A new identification key is provided to all known Chinese representatives of the subgenus Cardiobioramix.